Environmental health, health outcomes, poverty and sustainable development in developing countries - Waziri, Salisu Ibrahim (2018)
Safe drinking water and good sanitation are very important facilities to humanity especially to improve health outcomes and achieving sustainable development. There exists a large variation in accessibility of these facilities amongst the more developed (higher- and upper-middle income) and less developed (low- and lowermiddle income) countries. Therefore, socioeconomic indicators such as health outcomes, poverty and sustainable development could be largely affected as population get access to safe drinking and good sanitation. This study aims to estimate the impact of environmental health (access to safe drinking water and good sanitation) on health outcomes (under-five mortality) in 81 low- and lower-middle income countries in the world. The second objective examines the direct effect of environmental health on poverty in 81 low- and lowermiddle income countries. Also, it estimated the indirect effects of environmental health on poverty through labour-force productivity. While the third objective aims at to examine the impact of environmental health, under-five mortality, and poverty on sustainable development in 47 developing countries. Generalized method of moments (GMM) was employed to estimate the dynamic models in all the three objectives. The period of nine years was used in all the three models from 2008 to 2016. The results show that, access to safe drinking water and good sanitation are very critical determinants for reducing the prevalence of under-five mortality in developing countries (low- and lower-middle income countries). Interestingly, both results of difference and system GMM have indicated a negative relationship between access to safe drinking water and good sanitation and under-five mortality.This implies that as population get access to safe drinking water and good sanitation facilities, the prevalence of water-related diseases such as malaria, cholera, diarrhea and dengue would be reduced, hence the prevalence of under-five mortality would also declined. Regarding the second the objective, the result reveal that, access to safe drinking water and good sanitation also plays a significant role both direct and indirectly in poverty reduction in low- and lower-middle income countries. Both the direct and indirect links have indicated that access to safe drinking water and good sanitation is negatively related to poverty. The indirect relationship explained the conditional hypothesis, in which the marginal effect of the interaction term between labour-force productivity and access to safe drinking water and good sanitation. The result shows that reduction of poverty due to access to safe drinking water and good sanitation is conditional on the effectiveness of human capital (labour-force productivity). Finally, the third objective discloses a contribution to sustainable development literature by providing empirical link between environmental health, under-five mortality and poverty with sustainable development using the Green Solow growth model. The estimated results revealed that, environmental health especially access to safe drinking water is an essential factor for achieving sustainable development, with a positive relationship amongst them. Carbon dioxide (CO2) emission and under-five mortality were found to be negatively related to sustainable development in developing countries. This study has also utilised the three indicators of governors (control of corruption, regulatory qualities and governance effectiveness) in the analysis. The results of difference and system GMM suggested that governance indicators are important and crucial factors for achieving sustainable development in developing countries. For policy implication, the study suggest that, governments in low- and lowermiddle income countries should ensure the provision safe drinking water for all. Also enforcement of environmental sanitation laws should be maintained. Secondly, to alleviate poverty, the study recommend Government policies especially fiscal policy should focused on provision of safe drinking water amongst households/communities as to overcome the suffering of people toward waterpoverty nexus. Enhancing productivity of labour through human capital investment is also recommended to mitigate poverty in those countries. Finally, Government of developing countries should enact policies that geared towards increasing economic growth and development alone side with ensuring quality of environment. Agreements signed by various governments during Rio-De Janerio (Rio- Summit) and beyond toward adopting sustainable practice in managing natural resources like water and reduction in green-house gasses globally should be implemented.